2011
DOI: 10.3285/eg.60.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Novel methodological approaches in loess research – interrogating biomarkers and compound-specific stable isotopes

Abstract: Abstract. Löss-Paläoboden Sequenzen sind wichtige terrestrische Archive für die Rekonstruktion der quartären Landschafts- und Klimageschichte. Die Entwicklung neuer, quantitativerer Paläoklima-Proxies könnte in den kommenden Jahren eine neue Ära in der Lössforschung einleiten. Dieser Review-Artikel stellt die Prinzipien, die zugrunde liegende Analytik, und erste Anwendungsbeispiele für einige dieser Proxies vor, welche derzeit entwickelt werden. Wir diskutieren das Potential von (i) pflanzenwachsbürtigen n-Alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 111 publications
(131 reference statements)
0
20
0
1
Order By: Relevance
“…When considering that both δ 13 C TOC and TOC/N values of terrestrial organic matter are additionally affected by mineralisation and degradation, resulting in more positive δ 13 C TOC values and lower TOC/N ratios (e.g. Zech et al, 2007), a straightforward interpretation of those proxies seems to be challenging. Similarly, δ 15 N has been investigated as proxy for sedimentary organic matter origin (Meyers and Ishiwatari, 1993;Meyers and Lallier-Vergés, 1999;Wolfe et al, 1999).…”
Section: Conceptual Framework Of the Coupledmentioning
confidence: 99%
See 2 more Smart Citations
“…When considering that both δ 13 C TOC and TOC/N values of terrestrial organic matter are additionally affected by mineralisation and degradation, resulting in more positive δ 13 C TOC values and lower TOC/N ratios (e.g. Zech et al, 2007), a straightforward interpretation of those proxies seems to be challenging. Similarly, δ 15 N has been investigated as proxy for sedimentary organic matter origin (Meyers and Ishiwatari, 1993;Meyers and Lallier-Vergés, 1999;Wolfe et al, 1999).…”
Section: Conceptual Framework Of the Coupledmentioning
confidence: 99%
“…With regard to the sugar biomarkers, they were previously studied in detail by Hepp et al (2016). According to the authors' own results and a compilation from the literature (including, e.g., Jia et al, 2008;Prietzel et al, 2013;Zech et al, 2012Zech et al, , 2014b, relatively high amounts of arabinose are a good indicator of a primarily terrestrial origin (higher vascular plants) of the sugars. This interpretation is in agreement with the Gemündener Maar being a small lake with densely forested steep crater walls (Fig.…”
Section: Conceptual Framework Of the Coupledmentioning
confidence: 99%
See 1 more Smart Citation
“…n-alkanes are important constituents of plant leaf waxes (Kolattukudy, 1970), where they serve to protect plants against water loss by evaporation as well as from fungal and insect attacks (Eglinton and Hamilton, 1967;Koch et al, 2009). Due to their recalcitrant nature, they are often well preserved in sedimentary archives and used as biomarkers (also called molecular fossils) in paleoclimate and environmental studies (Eglinton and Eglinton, 2008;Glaser and Zech, 2005;Zech et al, 2011c). The potential of n-alkanes for chemotaxonomic studies has been suggested based on the finding that the homologues C 27 and C 29 are sourced pre-dominantly from trees and shrubs, whereas the homologues C 31 and C 33 are sourced predominantly from grasses and herbs (Maffei, 1996;Maffei et al, 2004;Rommerskirchen et al, 2006;Schäfer et al, 2016;Zech, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Potential pitfalls when applying n-alkane proxies in paleovegetation studies should not be overlooked. For instance, (Bush and McInerney, 2013) caution against the chemotaxonomic application of n-alkanes because of high n-alkane pattern variability within graminoids and woody plants (Schäfer et al, 2016) emphasized the need for establishing regional calibration studies and Zech et al, (2011aZech et al, ( , 2013 point to degradation affecting n-alkane proxies.…”
Section: Introductionmentioning
confidence: 99%